Intraretinal cysts are the most relevant prognostic biomarker in neovascular age-related macular degeneration independent of the therapeutic strategy. Issue 12 (30th July 2014) - Ritter, Markus; Simader, Christian; Bolz, Matthias; Deák, Gábor G; Mayr-Sponer, Ulrike; Sayegh, Ramzi; Kundi, Michael; Schmidt-Erfurth, Ursula M
Abstract : Background/aims: To investigate the impact of antiangiogenic monotherapy and photodynamic therapy (PDT) as add-on strategy on retinal morphology, and to analyse prognostic biomarkers for visual outcome and retreatment frequency in neovascular age-related macular degeneration (nAMD). Methods: 255 patients participating in the MONT BLANC study were evaluated. Patients were randomised to receive as-needed ranibizumab monotherapy or combination therapy (verteporfin PDT and ranibizumab). Outcome measures included visual acuity (VA), retinal morphology assessed by optical coherence tomography and retreatment frequency. Results: The proportion of scans showing intraretinal cysts (IRC) or subretinal fluid (SRF) decreased more intensively in the combination than in the monotherapy group. Pigment epithelial detachments (PED) decreased significantly only in the combination group. Patients with IRC presented the lowest initial VA, and IRC had the strongest negative predictive value for functional improvement in both groups. SRF showed a predictive value for a higher number of ranibizumab injections (combination, +0.9; monotherapy, +0.8) and a higher number of PDT treatments in the combination group (+0.3). PED was associated with a higher number of ranibizumab injections only in the monotherapy group (+1.2). Conclusions: Combination and monotherapy showed a distinct response pattern for morphological parameters in nAMD. IRC was the only relevant prognostic parameter for functional outcome. Trial registration number: NCT00433017.